The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1128/iai.01285-07
|View full text |Cite
|
Sign up to set email alerts
|

αB-Crystallin Protects Retinal Tissue during Staphylococcus aureus - Induced Endophthalmitis

Abstract: Bacterial infections of the eye highlight a dilemma that is central to all immune-privileged sites. On the one hand, immune privilege limits inflammation to prevent bystander destruction of normal tissue and loss of vision. On the other hand, bacterial infections require a robust inflammatory response for rapid clearance of the pathogen. We demonstrate that the retina handles this dilemma, in part, by activation of a protective heat shock protein. During Staphylococcus aureus-induced endophthalmitis, the small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 40 publications
3
66
1
Order By: Relevance
“…At day-1 following AION, western blot analysis (Figure 1b-c) revealed an upregulation of aBC protein in the ON head and neuroretina compared with control eyes (n ¼ 4 experiments, Po0.03), but no significant change in the expression of class-III b-tubulin, a major component of the neuronal microtubule that is highly expressed in RGCs. Consistent with the idea that aBC is important in inflammation, 15,21 we found that on post-ischemia day 3, there was increased ON head Iba-1 staining (data not shown, n ¼ 5, see Figure 2), which suggested microglial activation, and elevated GFAP expression (data not shown, n ¼ 5, see Figure 2), which correlated with astrocytic activation. These findings resembled changes after laser-induced photochemical thrombosis in the retina 22 and axonal ischemia near the retina-ON junction 23 and the brain.…”
Section: Early Post-aion Upregulation Of Abcsupporting
confidence: 71%
“…At day-1 following AION, western blot analysis (Figure 1b-c) revealed an upregulation of aBC protein in the ON head and neuroretina compared with control eyes (n ¼ 4 experiments, Po0.03), but no significant change in the expression of class-III b-tubulin, a major component of the neuronal microtubule that is highly expressed in RGCs. Consistent with the idea that aBC is important in inflammation, 15,21 we found that on post-ischemia day 3, there was increased ON head Iba-1 staining (data not shown, n ¼ 5, see Figure 2), which suggested microglial activation, and elevated GFAP expression (data not shown, n ¼ 5, see Figure 2), which correlated with astrocytic activation. These findings resembled changes after laser-induced photochemical thrombosis in the retina 22 and axonal ischemia near the retina-ON junction 23 and the brain.…”
Section: Early Post-aion Upregulation Of Abcsupporting
confidence: 71%
“…Inflammation is a clear component of the pathophysiology of diabetes and diabetic retinopathy in which Hsps could play a key role. Studies of the impact of endophthalmitis and uveitis in alpha-crystallin knockout animals strongly suggest that alpha-crystallin overexpression could be a special protective mechanism that preserves retinal cells from death during inflammation [30,78]. However, detection of antibodies against alphaA-and/or alphaBcrystallins in serum from uveitis or multiple sclerosis patients as well as in mice with experimental autoimmune encephalomyelitis [24,79] could also suggest that alphacrystallin upregulation in these diseases becomes maladaptive and exacerbate the inflammatory response leading to neurodegeneration.…”
Section: Regulation Of Functionmentioning
confidence: 98%
“…In fact, recombinant αB-crystallin protein reduced the number of inflammatory foci and apoptotic glial cell death in the model (7). Whiston et al identified the critical role of αB-crystallin in protecting the retina during inflammation using a murine model of Staphylococcus aureus-induced endophthalmitis (8). These results suggest αB-crystallin may be a therapeutic target for human inflammatory diseases.…”
Section: Discussionmentioning
confidence: 81%
“…We recently demonstrated that αA-crystallin was up-regulated in the diabetic retina (5), which is possibly correlated with protection of retinal cells from apoptotic signals during progression of diabetic retinopathy. Moreover, a variety of experimental inflammatory models have revealed that up-regulation of αA-or αB-crystallin protected specific cells from apoptotic signals associated with inflammation (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%